P1 4 Beau and Arrow - Blue, R.; Blase, L. L.; Kelly, C. L.; Thompson, J. R. G. (Physics Special Topics, 2023)
This paper explores the possibility of firing an arrow to split a stationary arrow in half. Considering Newtonian projectile motion, the initial velocity of the arrow was determined to be 125 ms−1 . This is within the expected range of velocities for recurve bow and longbow archers. An optimum firing angle was found to be 44.6◦ . Forces acting within the system demonstrate that an arrow made of iron and poplar could split the stationary arrow under the right conditions.